TRAINING ON COMPOSTING COCOA LEAF WASTE (Theobroma cacao) IN WATES VILLAGE, Sumbergempol District, Tulungagung Regency - Fatimah, Fatimah; Martha, Rahma Diyan (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Chocolate (Theobroma cacao) is one of the largest plantation commodities in Indonesia. Along with the increase in cocoa exports, expansion of cocoa plantations was carried out to increase the number of exports and meet demand for cocoa in the domestic market. Wates Village, located in Sumbergempol District, is one of the villages that has a community-owned cocoa plantation. However, one of the problems faced by cocoa plantations is the large amount of leaf waste produced every day. Improper processing of cocoa leaf waste can cause environmental pollution. Based on this, education and training regarding making compost from cocoa leaf waste is needed for residents. With this guidance and training, it is hoped that residents will be aware of the negative impact of improper processing of cocoa leaf waste on the environment, and can utilize this waste into compost which will later be used to meet residents' fertilizer needs. Because the majority of residents in the village are farmers.